Genetic differentiation among distinct karyomorphs of the wolf fish Hoplias malabaricus species complex (Characiformes, Erythrinidae) and report of unusual hybridization with natural triploidy. Issue 5 (26th September 2014) - Utsunomia, R.; Pansonato Alves, J. C.; Paiva, L. R. S.; Costa Silva, G. J.; Oliveira, C.; Bertollo, L. A. C.; Foresti, F.
<x xml:space="preserve">Abstract</x> In this study, genetic differentiation between karyomorphs A (2n = 42) and D (2n = 39/40) of the wolf fish Hoplias malabaricus, which is comprised of several cryptic species that present a wide variety of diploid chromosome numbers and sex chromosome systems, resulting in the identification of seven distinct karyomorphs (A–G), was investigated using a combination of molecular and cytogenetic tools. Deep sequence divergences for both karyomorphs were observed and indicate a long period of reproductive isolation between karyomorphs A and D. Additionally, one individual with 61 chromosomes was identified, which, as far as is known, is the first case of natural triploidy resulting from the hybridization between these highly differentiated karyomorphs of H. malabaricus. Molecular and cytogenetic analyses revealed that this allotriploid specimen carries two sets of maternal chromosomes from karyomorph D (2n = 40) and one set of chromosomes from karyomorph A (n = 21). Moreover, ribosomal sites and active nucleolus organizer regions from both parental contributors were found in the triploid hybrid. Considering the significant genetic distances between karyomorphs A and D, one of the primary reasons for the lack of recurrent reports of hybridization in the H. malabaricus species complex may be due to post‐zygotic barriers, such as hybrid sterility or unviability.